Signs of nature in Bediuzzaman Said Nursi: A significant contribution to Islamic semiotics - Khalawi, Hasan; Zarkasyi, Hamid Fahmy; Rahardjo, Mudjia (LITERA, 2024)
In the life circle, humans always produce, receive, and search for the meaning of signs. The meanings have ultimate value concerning Islamic worldview which then determines human salvation. Therefore, these issues are very important to research. The researchers worked in a deductive-inductive approach: a quasi-qualitative method characterized by the use of theories to be reconstructed after critical dialogues aimed at revealing the meanings of the natural signs based on an Islamic worldview and proposing a model of the Islamic theory of sign. The subject of this research is the books of Risale-i Nur as the representation of the Islamic worldview. Further, the techniques of the data collection are (1) preparing the domain (2) constituting the taxonomy of the data; (3) note-taking in the text of the Risale-i Nur. Furthermore, the latent content analysis was employed. The researchers categorized qualitative textual data into clusters of similar entities, or conceptual categories, to identify consistent patterns and relationships between themes. Finally, the researchers concluded that the meanings of the natural signs in the Risale-i Nur are the manifestation of the perfection of God's Names. Moreover, the significant contribution of the Risale-i Nur to Islamic semiotics is revealed and proposed.